2020
DOI: 10.1186/s41983-020-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

Salivary alpha-synuclein (total and oligomeric form): potential biomarkers in Parkinson’s disease

Abstract: Background: Parkinson's disease (PD) is one of the most common degenerative diseases of the central nervous system (CNS). Alpha-synuclein (A-syn) plays a critical role in the pathogenesis of PD. The close relation between the salivary glands and the CNS could render the A-syn secretions in the saliva useful biomarkers for PD. Aim of the work: To study the salivary A-syn levels in a cohort of PD Egyptian patients and to correlate these Asyn levels with the patients' clinical data and disease severity. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…The authors suggested that the decrease in total α-synuclein in saliva in PD subjects could partly be accounted for by the oligomerization of monomeric α-synuclein. Similar findings were reported by Shaheen et al (2020) , which also showed a positive correlation between the level of o-α-syn and disease duration; further, in PD patients, higher levels of o-α-syn were seen in bradykinesia and rigidity-dominant than in tremor-dominant phenotypes. Another study measured the salivary total α-synuclein and o-α-syn between controls and PD cases and analyzed single nucleotide polymorphisms or SNP variants of SNCA in the PD group ( Kang et al, 2016 ).…”
Section: α-Synuclein As a Biomarkersupporting
confidence: 88%
“…The authors suggested that the decrease in total α-synuclein in saliva in PD subjects could partly be accounted for by the oligomerization of monomeric α-synuclein. Similar findings were reported by Shaheen et al (2020) , which also showed a positive correlation between the level of o-α-syn and disease duration; further, in PD patients, higher levels of o-α-syn were seen in bradykinesia and rigidity-dominant than in tremor-dominant phenotypes. Another study measured the salivary total α-synuclein and o-α-syn between controls and PD cases and analyzed single nucleotide polymorphisms or SNP variants of SNCA in the PD group ( Kang et al, 2016 ).…”
Section: α-Synuclein As a Biomarkersupporting
confidence: 88%
“…In conclusion, this study confirmed the hypothesis of evaluating the total α-synuclein/oligomeric α-synuclein ratio as a possible biomarker in the diagnosis of PD. However, this ratio did not correlate with the severity of PD [41].…”
Section: Salivary Biomarkers In Parkinson's Diseasementioning
confidence: 70%
“…Potential circulating biomarkers for diagnosis, prognosis, and monitoring have been identified in salivary secretions for various diseases, including PD, AD, Sjögren’s syndrome, and oral cancer. 10 14 , 31 , 43 , 52 54 Among neurodegenerative diseases, like PD, the critical role of oxidative stress in disease pathogenesis have led to increasing research in the use of oxidatively modified nucleic acids, lipids, proteins, and antioxidants such as HO-1, advanced glycation end products, and reduced glutathione as salivary redox biomarkers for diagnostic or prognostic markers of disease. 54 58 Saliva has several advantages in comparison to other biofluids for biomarker research such as its non-invasive method of fluid acquisition, the non-extensive requirement for personnel training for saliva specimen collection, and salivary composition being reflective of blood or CSF composition.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Several chemical analytes in saliva have been investigated as potential biomarkers for PD, including α-synuclein, protein deglycase DJ-1, and heme oxygenase-1 (HO-1), an inducible enzyme that degrades heme to biliverdin, ferrous iron, and carbon monoxide. [10][11][12][13][14][15][16] The HMOX1 gene contains a panoply of regulatory elements that allows it to respond to numerous stressors such as heme, dopamine, nitric oxide, TH1 cytokines, and other oxidative and inflammatory stimuli. [17][18][19] During acute oxidative stress-induced neurotoxicity, HO-1 has been shown to have cytoprotective effects; however, chronic expression of HO-1 has been proposed to be detrimental to cell health and survival.…”
Section: Introductionmentioning
confidence: 99%